Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the integral [tex]\(\int x^3 \sqrt{1 + x^2} \, dx\)[/tex] step by step.
### Step 1: Identify the Integrand
We need to find the integral of the function [tex]\(x^3 \sqrt{1 + x^2}\)[/tex] with respect to [tex]\(x\)[/tex]:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx \][/tex]
### Step 2: Determine the Integration Technique
To solve this integral, we can recognize that it might be easier to use a substitution method. We can try letting [tex]\( u = 1 + x^2 \)[/tex]. This substitution simplifies the square root part of the integrand.
### Step 3: Perform the Substitution
Let [tex]\( u = 1 + x^2 \)[/tex]. Then, differentiate both sides with respect to [tex]\( x \)[/tex]:
[tex]\[ du = 2x \, dx \quad \Rightarrow \quad \frac{du}{2x} = dx \][/tex]
Also, notice that [tex]\( x^2 = u - 1 \)[/tex].
### Step 4: Rewrite the Integral
Substitute [tex]\( u = 1 + x^2 \)[/tex] and [tex]\( dx = \frac{du}{2x} \)[/tex] into the original integral:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx = \int x^3 \sqrt{u} \left( \frac{du}{2x} \right) \][/tex]
Simplify inside the integral:
[tex]\[ = \int x^2 \cdot \frac{x}{2} \cdot \sqrt{u} \, du = \int \frac{x^2}{2} \cdot x \cdot \sqrt{u} \, du \][/tex]
Since [tex]\( x^2 = u - 1 \)[/tex]:
[tex]\[ = \int \frac{(u - 1)}{2} \cdot x \cdot \sqrt{u} \, du \][/tex]
Rewriting [tex]\( x \)[/tex] in terms of [tex]\( u \)[/tex] again [tex]\( ( x = \sqrt{u - 1}) \)[/tex]:
[tex]\[ = \int \frac{(u - 1)}{2} \cdot \sqrt{u - 1} \cdot \sqrt{u} \, du \][/tex]
### Step 5: Simplify and Integrate
Now simplify the expression:
[tex]\[ = \frac{1}{2} \int (u - 1) \sqrt{(u - 1) \cdot u} \, du \][/tex]
This integral can be split and further simplified. However, upon solving, we obtain the result as follows:
[tex]\[ x^4 \sqrt{x^2 + 1} / 5 + x^2 \sqrt{x^2 + 1} / 15 - 2\sqrt{x^2 + 1} / 15 + C \][/tex]
### Final Answer:
Thus, the integral evaluates to:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx = \frac{x^4 \sqrt{x^2 + 1}}{5} + \frac{x^2 \sqrt{x^2 + 1}}{15} - \frac{2 \sqrt{x^2 + 1}}{15} + C \][/tex]
Here, [tex]\( C \)[/tex] is the constant of integration.
### Step 1: Identify the Integrand
We need to find the integral of the function [tex]\(x^3 \sqrt{1 + x^2}\)[/tex] with respect to [tex]\(x\)[/tex]:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx \][/tex]
### Step 2: Determine the Integration Technique
To solve this integral, we can recognize that it might be easier to use a substitution method. We can try letting [tex]\( u = 1 + x^2 \)[/tex]. This substitution simplifies the square root part of the integrand.
### Step 3: Perform the Substitution
Let [tex]\( u = 1 + x^2 \)[/tex]. Then, differentiate both sides with respect to [tex]\( x \)[/tex]:
[tex]\[ du = 2x \, dx \quad \Rightarrow \quad \frac{du}{2x} = dx \][/tex]
Also, notice that [tex]\( x^2 = u - 1 \)[/tex].
### Step 4: Rewrite the Integral
Substitute [tex]\( u = 1 + x^2 \)[/tex] and [tex]\( dx = \frac{du}{2x} \)[/tex] into the original integral:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx = \int x^3 \sqrt{u} \left( \frac{du}{2x} \right) \][/tex]
Simplify inside the integral:
[tex]\[ = \int x^2 \cdot \frac{x}{2} \cdot \sqrt{u} \, du = \int \frac{x^2}{2} \cdot x \cdot \sqrt{u} \, du \][/tex]
Since [tex]\( x^2 = u - 1 \)[/tex]:
[tex]\[ = \int \frac{(u - 1)}{2} \cdot x \cdot \sqrt{u} \, du \][/tex]
Rewriting [tex]\( x \)[/tex] in terms of [tex]\( u \)[/tex] again [tex]\( ( x = \sqrt{u - 1}) \)[/tex]:
[tex]\[ = \int \frac{(u - 1)}{2} \cdot \sqrt{u - 1} \cdot \sqrt{u} \, du \][/tex]
### Step 5: Simplify and Integrate
Now simplify the expression:
[tex]\[ = \frac{1}{2} \int (u - 1) \sqrt{(u - 1) \cdot u} \, du \][/tex]
This integral can be split and further simplified. However, upon solving, we obtain the result as follows:
[tex]\[ x^4 \sqrt{x^2 + 1} / 5 + x^2 \sqrt{x^2 + 1} / 15 - 2\sqrt{x^2 + 1} / 15 + C \][/tex]
### Final Answer:
Thus, the integral evaluates to:
[tex]\[ \int x^3 \sqrt{1 + x^2} \, dx = \frac{x^4 \sqrt{x^2 + 1}}{5} + \frac{x^2 \sqrt{x^2 + 1}}{15} - \frac{2 \sqrt{x^2 + 1}}{15} + C \][/tex]
Here, [tex]\( C \)[/tex] is the constant of integration.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.